Subjective Well-Being Among Unemployed Early Adults: The Role of Optimism and Unemployment Duration Across Genders - Thomas Ari Wicaksono; Margaretha Sih Setija Utami (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Subjective well-being (SWB) is an essential aspect of life. The higher a person's well-being level, the higher their quality of life. This research aims to know the correlations between the duration of unemployment, gender, and optimism with the subjective well-being of unemployed early adults. The research hypotheses are: 1) There is a relationship between duration of unemployment and optimism and subjective well-being; 2) There are many differences in subjective well-being between male and female unemployed early adults. The subjects of this research are early adults who are unemployed or starting a business and currently reside in Central Java. The subjects involved in this research are 159 respondents. The measuring instruments used are an optimism scale and a subjective well-being scale created by researchers. Both measuring instruments have been tested for validity and reliability. The data analysis techniques are multiple regression analysis and t-test. The research results show 1) there is a correlation between the duration of unemployment and optimism with subjective well-being (R= 0.737, Adjusted R Square = 0.537, F: 92.477, p< 0.05); 2). There is no significant difference in subjective well-being between males and females unemployed in early adulthood (t=1.453, p>0.05) Kesejahteraan subjektif adalah aspek penting dalam kehidupan. Semakin tinggi tingkat kesejahteraan seseorang, maka semakin tinggi pula kualitas hidupnya. Penelitian ini bertujuan untuk mengetahui hubungan antara lama menganggur, jenis kelamin, dan optimisme dengan subjective well-being pada dewasa awal yang menganggur. Hipotesis dari penelitian ini adalah: 1) Terdapat hubungan antara durasi menganggur dan optimisme dengan kesejahteraan subjektif; 2) Terdapat perbedaan kesejahteraan subjektif antara laki-laki dan perempuan dewasa awal yang menganggur. Subjek penelitian ini adalah orang dewasa awal yang sedang menganggur atau memulai usaha dan berdomisili di Jawa Tengah. Subjek yang terlibat dalam penelitian ini berjumlah 159 responden. Alat ukur yang digunakan adalah skala optimisme dan skala kesejahteraan subjektif yang dibuat oleh peneliti. Kedua alat ukur tersebut telah diuji validitas dan reliabilitasnya. Teknik analisis data yang digunakan adalah analisis regresi berganda dan uji-t. Hasil penelitian menunjukkan 1) ada hubungan antara durasi menganggur dan optimisme dengan kesejahteraan subjektif (R= 0,737, Adjusted R Square = 0,537, F: 92,477, p0.05)